ANALISIS INFLUENCER MARKETING PADA PLATFORM MEDIA SOSIAL INSTAGRAM HOTEL ROYAL PALM JAKARTA - Adellia, Tabitha Putri; Abdullah, Taufik (Puslitabmas Batam Tourism Polytecnic, 2024)
This study investigates the role of influencer marketing on social media, specifically Instagram, as a strategic marketing approach in the hospitality industry, with a focus on Hotel Royal Palm Jakarta. Recognizing the importance of social media in contemporary travel information access, the research highlights how hotels can leverage influencers to establish and maintain strong customer relationships. The hotel utilizes influencer marketing to promote its affordable